The ordinary management of small businesses: another look on the management in organizational studies (Revista de Administração, 2014)
This paper aims to present the ordinary management who escapes the managerialism parameters in order to focus on the daily life of the ordinary man who runs ordinary businesses, family enterprises, with their social relations, their way of organizing their business, their survival strategies, their uses and meanings of spaces – business and family – and the network of relationships woven by them. In this paper we question the management prospect as one based on knowledge seen as pure or neutral (restricted to rational), absolute and universal (excluding other competitors knowledge) and triumphed politically and economically through management technologies. In contrast to this position, we argued in this paper that one must take into account aspects of historical, social, cultural and identity that differentiate subjects and in everyday practice pluralized the management. So there are other approaches that can contribute to the advancement of scientific knowledge in the field of organizational studies, being the ordinary management one of these approaches.